Media and socio economic development in Northern Nigeria - Pate, Umaru A.; Dauda, Sharafa (Universiti Kebangsaan Malaysian, 2013)
This article discusses the crucial role of the mass media, peculiarly TV and radio, in reversing the burgeoning socioeconomic challenges of Northern Nigeria. It argues that mainstreaming global development initiatives and integrating the specific regional, state and national goals and policies in line with needs and expectations of the people can guarantee their freedom of opportunities and prosperity. It proposes: true democracy, good governance, accountability and transparency, human rights, increased political will and support for community radio for community needs, among othersas key enabling environment. It adds that media organizations and professionals need to resist political pressures and interferences to reflect the true feelings and needs of the people; institutionalize investigative/advocacy journalism to expose corruption and mismanagement of public resources by monitoring, criticizing, analyzing and interpreting public budget, expenditure, policy and implementation of global, national and local development initiatives instead of the norm of being appendages of governments. The article suggests further that the media in Northern Nigeria can strengthen their internal competence and ethical capacity for professionalism and adopt peace journalism in coverage of diversity and conflict, in their programming to illuminatethe cherished values of the people and to guide and direct social conduct and behaviour for sustainable development.